Benefits of intermediate-layer formation at the interface of Nb/Cu and Ta/Cu explosive clads. (15th March 2019) - Parchuri, PradeepK.; Kotegawa, Shota; Yamamoto, Hajime; Ito, Kazuhiro; Mori, Akihisa; Hokamoto, Kazuyuki
Abstract: A systematic, comparative study was carried out to quantitatively characterize the bending strength of wavy interfaces with and without an intermediate layer (IL) in Nb/Cu and Ta/Cu explosive clads. The clads having wavy interfaces with and without an IL were obtained at horizontal high and low collision velocities (HCV and LCV) in the explosive welding, respectively. The stress-strain curves of all the clads were similar in three-point bending tests, but the clads with an IL exhibited higher bending stress than those without an IL. Moreover, cracks were observed in the Nb plate of Nb/Cu clads without an IL, but no cracks in that with an IL. TEM observation confirmed coexistence of ultrafine refractory metal and Cu phases in the ILs. In addition, the Ta-Cu-based intermetallic compound or dodecagonal quasicrystal, which is a non-equilibrium phase, were also observed along with coexistence of Ta and Cu phases in the ILs of Ta/Cu interface. Cladding at HCV and a lower collision angle assisted in resultant less strain in refractory metal plates near the joint interfaces than those at LCV, due to IL formation. The ILs assisted in obtainment of interfaces of higher hardness, leading to higher bending-stress clads without losing large elongation. Graphical abstract: Unlabelled Image Highlights: An intermediate layer increased bending strength of Nb/Cu and Ta/Cu clads without losing large elongation. Coexisting ultrafine refractory metal and Cu phases increased intermediate layer hardness, leading to high bending stress. The Ta-Cu-based intermetallic compound or Ta-Cu-based dodecagonal quasicrystal phases in Cu matrix was a new finding. Formation of an intermediate layer assisted in resultant less strain refractory metal plates near the joint interfaces. Shock wave damage to base metal plates has been reduced by forming an intermediate layer at the interface of Nb/Cu clads.